Pelatihan Kepemimpinan Terhadap Kinerja Karyawan di Salim Herbal Semarang - Dyah Purwaningrum; Sutaat Sutaat (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Leadership is the process of influencing other people, subordinates, or followers to achieve the organization's desired goals. In general, leadership can be divided into three leadership models practiced by managing companies. Each model has its own uniqueness; some are closely related to the nature or character of the person, and some even arise as a result of the learning process. Realizing the importance of the role of a leader in achieving the goals of an organization, it can be said that the success or failure experienced by most organizations is determined by the quality of leadership played by the leader of the organization. This training partner aims to increase the employees' understanding and abilities as leaders in the company's divisions. Through this training, it is hoped that employees will be able to increase work morale within themselves and their team members, become effective leaders, and create synergistic collaborations. Through training, it is hoped that one can maximize one’s leadership abilities to become a good leader, intelligent, critical, strategic, able to face challenges, and focus on goals.